HUBUNGAN TINGKAT PENGETAHUAN PERAWAT DENGAN PELAKSANAAN IDENTIFIKASI PASIEN DI RUANGAN BEDAH DAN UROLOGI RSUD TOTO KABILA - Abubakar, Windha; Zainuddin, Zainuddin; Sulaiman, Ibrahim (Medical and Health Journal, 2025)
Patient safety is a crucial aspect in health services, with proper patient identification can prevent medical errors. Nurses' knowledge of patient identification procedures plays an important role in effective implementation. The purpose of this study was to analyze the relationship between the level of nurses' knowledge and the implementation of patient identification in the Surgery and Urology rooms of Toto Kabila Hospital. This research method uses observational analytic with a cross-sectional approach, involving 31 nurses as samples taken using the total sampling technique. The instruments used were a questionnaire to measure knowledge and an observation sheet to assess the implementation of patient identification. The results showed a significant relationship between the level of knowledge and the implementation of patient identification (p-value 0.000, r = 0.968). The conclusion of this study is that increasing nurses' knowledge is very important to improve patient safety. The suggestion given is the need for routine training and socialization regarding patient safety for new nurses so that they can carry out patient identification properly.